2015
DOI: 10.1111/cgf.12603
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Eye Gaze in Virtual Agents, Social Robotics and HCI: Behaviour Generation, User Interaction and Perception

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(92 citation statements)
references
References 229 publications
0
91
0
1
Order By: Relevance
“…Just below humans on the spectrum are virtual agents, which have the potential for extremely high levels of behavioral realism. By nature of being animated, virtual agents can mimic human eye capabilities with greater precision than physical robots, though computationally encoding biologically realistic gaze behavior is an active area of research (Ruhland et al, 2015). While some virtual agents are implemented with complex, biologically faithful models of muscle movement that control eye motion, others use motion generators that are less consistent with the underlying biology (Ruhland et al, 2015), so there is a range of possible realism within the virtual agent literature.…”
Section: Robot Appearancementioning
confidence: 99%
“…Just below humans on the spectrum are virtual agents, which have the potential for extremely high levels of behavioral realism. By nature of being animated, virtual agents can mimic human eye capabilities with greater precision than physical robots, though computationally encoding biologically realistic gaze behavior is an active area of research (Ruhland et al, 2015). While some virtual agents are implemented with complex, biologically faithful models of muscle movement that control eye motion, others use motion generators that are less consistent with the underlying biology (Ruhland et al, 2015), so there is a range of possible realism within the virtual agent literature.…”
Section: Robot Appearancementioning
confidence: 99%
“…The research in virtual agents has shown a significant need for embodiment in virtual social interactions (Ruhland et al, 2015). Many studies supplement qualitative interviews and observer notes with quantitative data (Biocca and Nowak, 2001;Smith and Harrison, 2001;Dautenhahn, 2001), such as toward understanding ownership of sub-components of embodiment (Kilteni et al, 2012) and administering POMS questionnaire before and after completing an activity (Garau et al, 2005).…”
Section: Virtual Artificial Agentsmentioning
confidence: 99%
“…A NPC is a kind of social robots used to manage learners' communication practices and thus helps to simulate social contexts similar to those in the real world. Contrary to the importance of NPC as demonstrated in prior studies [2,3], defining how NPCs in VR-based social l skill training need to be applied is still elusive. Moreover, there is no clear overview of which design aspects should be addressed specifically for autistic children.…”
Section: Introductionmentioning
confidence: 87%